Carbon nanomaterials for the detection of pesticide residues in food: A review. (1st October 2022) - Mishra, Smriti; Mishra, Shivangi; Patel, Shiv Singh; Singh, Sheelendra Pratap; Kumar, Pradip; Khan, Mohd Akram; Awasthi, Himani; Singh, Shiv
Abstract: In agricultural fields, pesticides are widely used, but their residual presence in the environment poses a threat to humans, animals, insects, and ecosystems. The overuse of pesticides for pest control, enhancement of crop yield, etc. leaves behind a significant residual amount in the environment. Various robust, reliable, and reusable methods using a wide class of composites have been developed for the monitoring and controlling of pesticides. Researchers have discovered that carbon nanomaterials have a wide range of characteristics such as high porosity, conductivity and easy electron transfer that can be successfully used to detect pesticide residues from food. This review emphasizes the role of carbon nanomaterials in the field of pesticide residue analysis in different food matrices. The carbon nanomaterials including carbon nanotubes, carbon dots, carbon nanofibers, graphene/graphene oxides, and activated carbon fibres are discussed in the review. In addition, the review examines future prospects in this research area to help improve detection techniques for pesticides analysis. Graphical abstract: Image 1 Highlights: Use of carbon nanomaterials for pesticide residue analysis has been proven effective. They are highly porous, chemically inert and contain several functional groups. They are used as adsorbents and pesticide analyser in food samples. Future perception with carbon nanomaterials is even wider.